TINJAUAN TERHADAP IJIN MENDIRIKAN BANGUNAN (IMB) MASJID DI LAPANGAN KINIBALU BERDASARKAN PERATURAN DAERAH KOTA SAMARINDA NOMOR 34 TAHUN 2004 TENTANG BANGUNAN DALAM WILAYAH KOTA SAMARINDA - Christian, Julius (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
Abstract            The writing of this thesis research aims to find out the processes and constraints faced in the Building Construction Permit of Mosques in Kinibalu Field Based on the Regional Regulation of Samarinda City Number 34 of 2004 concerning Building Permit in the Territory of Samarinda. Writing This study uses juridical normative and empirical research methods derived from primary legal material and secondary legal material.            The results of the study indicate that the Mosque Building Permit in Kinibalu Field raises problems, it can be seen that there are still many residents who have not agreed with the project but the process of building the mosque has been done so that it is considered contrary to the Joint Minister of Home Affairs Regulation Number 9 and Number 8 of 2006 concerning the Guidelines for the Implementation of Regional Heads' Tasks in Maintaining Religious Harmony, Empowering the Religious Harmony Forum, and Establishing Houses of Worship, it is clearly written that special conditions in the process of establishing houses of worship must get the approval of local residents and the Forum for Harmony Religious Community (FKUB). The fact is that the construction of mosques in Kinibalu Field has still not received a recommendation from the Religious Harmony Forum (FKUB).Hopefully the results of this writing can help the Regional Government, especially in Samarinda City, the community and related parties in implementing the rule of law in the future.